Technological foundations and current status of a modified, low-risk form of competitive boxing (Box'Tag®) - Hahn, A. G.; Helmer, R. J. N.; Mackintosh, C.; Staynes, L. M.; Blanchonette, I. (Sports Technology, 2011)
Boxing-related activities are commonly used for fitness enhancement, but for many people fear of injury precludes participation in competitive boxing. Over the past six years, technological developments have contributed to the emergence in Australia of a modified, low-risk form of competitive boxing called Box'Tag®. The rules of Box'Tag® prohibit impacts to the head and any impacts above a moderate level of force. Contestants wear instrumented equipment that, in combination with a dedicated software package, allows automated impact detection and real-time display of scores. Participatory action research methods are being used to guide iterative technology refinements, with success evaluated based on feedback obtained through constant, direct interaction with the technology end-users. In concert with technological advances, the popularity of Box'Tag® is steadily increasing, with programmes now established in three Australian states and about to be initiated elsewhere. Box'Tag® is attracting demographically diverse participation and injury rates are low. Physiological and perceptual data recorded during contests show Box'Tag® to be a highly intensive activity and an excellent vehicle for building physical fitness. There is scope for further technological improvements, but the Box'Tag® initiative is already demonstrating potential to add a new dimension to boxing and has been adopted by Australian boxing authorities.